PENGARUH INFLASI, PRODUK DOMESTIK BRUTO (PDB) DAN NERACA PERDAGANGAN TERHADAP JUMLAH PENGANGGURAN DI INDONESIA: PENGARUH INFLASI, PRODUK DOMESTIK BRUTO (PDB) DAN NERACA PERDAGANGAN TERHADAP JUMLAH PENGANGGURAN DI INDONESIA - Rahmiati, Dyah Puspa; Panorama, Maya (Journal Of Islamic Ekonomic and Business, 2022)
Indonesia's digital economy is developing very rapidly, one of which is in the field of tourism. Advances in the digital economy will attract domestic and foreign tourists to Indonesia. The impact of advances in the digital economy is helping build the world's enterprises. Indonesian economic services are very high Indonesian tourism is not yet fully equipped with digital services. Analyzing the development of digital services using the method of predicting the extracted data can predict 10 years. In 2028, 465.1 trillion rupiah and 425.75 million trips will be spent. The techno planner was analyzed for the opportunity to create star-bridged tourism and archipelago tourists. This is naturally beneficial to Indonesia's economic growth by leveraging the digital economy in the age of the digital economy industry.